Importance of blood clotting tests in the diagnosis of haemolytic-uremic syndrome and experience with its treatment - Valnícek, S; Dolezel, J; Hrubanová, J; Habancová, M; Stejskal, J (Folia haematologica (Leipzig, Germany, 1988)
More than half of 33 children with HUS were less than a year old, 90% less than five. A constant laboratory finding was the presence of FDP in the blood and urine, and of the remaining tests the presence of erythrocyte fragments. The absence of thrombocytopenia does not eliminate HUS. Antiplatelet treatment was given to 94% of children, heparin to 94%, thrombolysis to 27% Precise evaluation of treatment would require a controlled prospective multicentre study.
Keywords: Hematologic Tests; kojenec; Infant; vyšetření krevní srážlivosti; streptokinasa; hemolyticko-uremický syndrom; Hemolytic-Uremic Syndrome; hydrokortison; hematologické testy; Child, Preschool; Hydrocortisone; Humans; předškolní dítě; fibrin-fibrinogen - produkty degradace; Dipyridamole; Streptokinase; Blood Coagulation Tests; Fibrin Fibrinogen Degradation Products; dipyridamol; lidé